Cost and resource implications with serum angiogenic factor estimation in the triage of preeclampsia - Schnettler, William T. (2013)
OBJECTIVE: To analyze the economic and resource implications of using plasma soluble fms-like tyrosine kinase-1 (sFlt1) and placenta growth factor (PlGF) measurements in preeclampsia evaluation and management. DESIGN: Retrospective cost analysis of our prospective cohort study. SETTING: Boston, Massachusetts (USA). POPULATION: Women (n=176) presenting to the hospital at <34 weeks’ gestation for evaluation of possible preeclampsia during 2009–2010. Cases without complete cost or outcome data (n=9) and re-enrollments (n=18) were excluded. METHODS: Modeled comparisons between the standard approach (combination of blood pressure, urinary protein excretion, alanine aminotransferase, and platelet counts) and a novel approach (ratio of plasma sFlt1 and PlGF) using actual hospital data converted to 2012 US dollars in accordance with Centers for Medicare and Medicaid Services. MAIN OUTCOME MEASURES: Direct two-week costs and resource utilization by groups having true or false positive and negative test results for adverse outcomes according to approach. RESULTS: The improved specificity of the novel approach decreased the proportion of women falsely labeled as test-positive from 42.3% (34.4% – 50.2%) to 4.0% (0.85% – 7.15%) and increased the proportion correctly labeled as test-negative from 23.5% (16.7% – 30.3%) to 61.7% (53.9% – 69.5%). This could potentially reduce average per-patient costs by $1,215. Substantial quantities of resources [47.2% (35.7% – 58.7%) of antenatal admissions and 72.5% (68.0% – 77.0%) of tests for fetal well-being] were unnecessarily used for women who were truly negative. A proportion of iatrogenic preterm deliveries among women with negative results was potentially avoidable representing further cost and resource savings. CONCLUSIONS: Clinical use of the plasma sFlt1 and PlGF ratio improves risk stratification among women presenting for preeclampsia evaluation and has the potential to reduce costs and resource utilization.